Universal Testbed for Algorithm Researches and Setting of Relay Protection and Automation in Power Systems with Distributed Generation and Renewable Energy Sources; Relay Protection and Automation (RPA 2018) - Askarov A. B. Alisher Bakhramzhonovich; Ruban N. Yu. Nikolay Yurievich; Andreev M. V. Mikhail Vladimirovich; Ufa R. A. Ruslan Alexandrovich; Suvorov A. A. Aleksey Aleksandrovich (2018, 2018)
Title screen